Letter from Carl D. Duncan to Patricia Whiting, March 18, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan discusses hotels for an upcoming trip and includes a list of potential locations in southern California for the trip.